Enhancing the efficiency of photovoltaic power system by submerging it in the rivers - Majid Valizadeh; Ibtihal Razaq Niama ALRubeei; Haider TH. Salim ALRikabi; Faisal Theyab Abed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
In light of the advanced technological development in the world, this study aims to use alternative energy for generating electric energy at the lowest cost. Solar cells are devices that have special operating conditions. The most important of these conditions are the temperature of cells and the intensity of solar radiation. Sometimes the climate condition does not match the ideal conditions used for operating solar cells in many regions around the world. Although the Middle East and Iraq in particular, is considered one of the sunniest areas in the world, solar energy cannot be relied upon to generate electric energy effectively because of the problem of high temperature in solar cells in the summer as well as the problem of dust. In this paper, a simple and economical method was designed to overcome the main problems in the operation of solar cells represented by high temperature in solar cells as well as the problem of dust accumulated on the surface of solar cells which impedes the entry of sunlight into those cells. The method is conducted by immersing the solar cells in running water at a distance that should be close to the surface of the water.